The dynamic of bank stock price and its fundamentals: Evidence from Indonesia - Hendrik Widjaja; Moch. Doddy Ariefianto (Cogent Economics & Finance)
This study examines the relationship between bank stock price and its selected fundamentals, namely, profitability, credit risk, and liquidity risk. Using the dynamic common correlated effect (DCCE) technique, we discover a mechanism error-correction between the stock price and the selected fundamentals. We estimate that the equilibrating process of stock price takes between 2.62 and 3.22 months. This study also provides significant support for hypotheses of the positive role of profitability (proxied by ROE and NIM) to bank stock price. Credit and liquidity risk measures do not significantly affect stock price.